(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Climate change is a reality that is experienced in different parts of the world. For this reason, a review was conducted to understand how fisheries and aquaculture can be promoted using climate-resilient and gender-inclusive measures. Nigerian fisheries and aquaculture sub-sector has high potential for development but is already experiencing climate change impacts like flooding and extreme droughts. The sector needs to play its role in contributing to the food, nutrition and livelihood security of the people of Nigeria. Developing climate-smart approaches with a gender-balanced perspective is key to ensuring success in mitigation of its effects. For this to be possible, the challenges limiting the growth of the sector must be addressed by the policy makers, researchers, and other stakeholders. Women need to be given the right space to play their roles in the fisheries and aquaculture sector just like the men. This will require some institutional framework and support on the part of the government to be achieved. If these are done fisheries and aquaculture will achieve the desired growth envisaged in the Code of Conduct for Responsible Fisheries and National Aquaculture Strategy.